Potential of melanin free ink as antioxidant and its application for preserving and predicting shelf life of salted-boiled milkfish. (16th December 2019) - Agustini, Tri Winarni; Hadiyanto, Hadiyanto; Amalia, Ulfah; Wijayantia, Ima
Antioxidant could be extracted and isolated from squid inks. Squid ink in the form of melanin free ink (MFI) could be act as an electron donor which can stabilise free radicals in lipid oxidation. Studies were carried out to assess the antioxidant activity of squid inks converted into MFI in different dilution and to optimise the extraction conditions for the application of MFI as an anti-oxidative agent on fish product. Three different concentrations of MFI extracts i.e., 0%, 0.75% and 1.5% were applied on soft-boned milkfish at 10°C, 20°C and 30°C temperature storages for nine days, with observation every three days. The results showed the animism of the ink through chemical parameters, antibacterial effect, and sensory analysis. MFI at a concentration of 0.75% was revealed to be effective in prolonging cold storage shelf life of soft boned milkfish, which was confirmed through comprehensive sensory analysis evaluation and measurement of chemical changes including water, protein, lipid and ash content. It was also discovered that 0.75% MFI significantly prolonged the cold storage period of soft boned milkfish until six days, indicating that it may be developed to be a natural preservative for marine products.